Metode Praktikum dengan Media Animasi Powerpoint : Pengaruh terhadap Motivasi Belajar Peserta Didik SMA Negeri 1 Belitang - Qurotul Aini; Siti Anisatur Rofiqah; Effendi Effendi (U-Teach: Journal Education of Young Physics Teacher, 2021)
The purpose of this study was to determine the effect of the application of the practicum method with PowerPoint animation media on the learning motivation of class XI science students at SMA Negeri 1 Belitang in the 2020/2021 academic year. The research design used a posttest-only control design. The population in this study were all students of class XI IPA SMA Negeri 1 Belitang totaling 216 students, and the research sample was 36 students of class XI IPA 2 as the experimental class and 36 students of class XI IPA 1 as the control class. The data collection technique in this study used a questionnaire and then analyzed using the t-test. Based on the results of the analysis, it is known that the level of learning motivation of experimental class students reaches 67% in the medium category and the level of learning motivation of control class students reaches 64% in the medium category. After the t-test was carried out, the results of tcount were 3.81 while ttable was 1.99. Because tcount was not between -ttable and +ttable i.e. -1.99, and +1.99 then, H0 is rejected and Ha is accepted. Hence, there is a significant influence on the application of the practicum method with PowerPoint animation media on the learning motivation of the students of class XI science at SMA Negeri 1 Belitang in the 2020/2021 academic year